Legitimacy‐Seeking Mechanisms in Product Innovation: A Qualitative Study*. Issue 3 (26th September 2016) - Bunduchi, Raluca
Abstract : Product innovation research adopts a rational choice perspective to examine resource allocation decisions for product innovation. This research emphasizes strategic alignment between the innovation and the organization as the key factor shaping these decisions. In contrast, organizational research suggests that to access resources, product innovations have to be perceived as legitimate by corporate sponsors. Legitimacy is rooted in alignment with the prevalent corporate norms, beliefs, and cultural model. Adopting an institutional perspective and relying on an in‐depth case study of three product innovations, this study explores legitimacy‐seeking behavior in product innovation. The findings indicate that the rational perspective emphasized in most product innovation research is complemented by efforts to seek both moral and cognitive legitimacy to resource product innovation. The study clarifies the critical role that the organizational context plays in triggering legitimacy‐seeking behavior. The analysis unpacks legitimacy‐seeking behavior, revealing patterns of legitimating mechanisms (lobbying, relationship building, and gathering feedback) that are deployed as part of legitimacy strategies (conforming, selecting, and manipulating) to achieve a range of legitimacy outcomes (pragmatic, moral, and cognitive). The analysis reveals the existence of a hierarchy of legitimacy outcomes as actors prioritize one type of legitimacy versus another. The study also finds interdependencies between mechanisms and strategies to reinforce particular outcomes as legitimacy‐seeking behavior evolves over time.